Multi-level issues in creativity and innovation - Mumford, Michael D.; Hunter, Samuel T.; Bedell-Avers, Katrina E. (Research in multi level issues ;, 2008)
Multi-Level Issues in Creativity and Innovation is Volume 7 of Research in Multi-Level Issues, an annual series that provides an outlet for the discussion of multi-level problems and solutions across a variety of fields of study. Using a scientific debate format of a key scholarly essay followed by two commentaries and a rebuttal, we present, in this series, theoretical work, significant empirical studies, methodological developments, analytical techniques, and philosophical treatments to advance the field of multi-level studies, regardless of disciplinary perspective.Similar to Volumes 1 through 6 (Yammarino & Dansereau, 2002, 2004, 2006; Dansereau & Yammarino, 2003, 2005, 2007), this volume, Volume 7, edited by Mumford, Hunter, and Bedell-Avers, contains five major essays with commentaries and rebuttals that cover a range of topics, but in the realms of creativity and innovation. In particular, the five critical essays offer extensive literature reviews, new model developments, methodological advancements, and some data for the study of creativity and social influence, innovation and planning, creativity and cognitive processes, sub-system configuration, and new venture emergence. While each of the major essays, and associated commentaries and rebuttals, is unique in orientation, they show a common bond in raising and addressing multi-level issues or discussing problems and solutions that involve multiple levels of analysis in creativity and innovation.It provides in-depth scholarly information on multiple level issues in organizations and time. It is international in scope.